Innovative PV Technologies for reducing electricity costs. Issue 1 (1st November 2022) - Gerardi, Cosimo; Bengasi, Giuseppe; Carbone, Lorenzo; Spampinato, Antonio; Rametta, Francesco; Ragonesi, Antonino; Izzo, Gaetano; Sciuto, Marcello; Foti, Marina; Bizzarri, Fabrizio
Abstract : Solar cells cost per Watt has decreased so quickly in the last years that photovoltaic (PV) module manufacturing costs cover only a small fraction of the total costs of a PV plant. Essentially, the installation and operation costs as well as the costs for the management of starting materials are the main factors today the most important levers for total costs decrease. PV technology has advanced towards both efficiency and average energy generation increasing by light capture optimization and losses minimization. This work analyses the state-of-the-art of PV technology for terrestrial application and discusses the perspectives for future development, which aims at overwhelming limitation posed by material properties. Higher focus is given to the most promising current technology such as silicon heterojunction solar cells and on future developments based on tandem cell approaches.